APP β-CTF triggers cell-autonomous synaptic toxicity independent of Aβ - Luo, Mengxun; Zhou, Jia; Sun, Cailu; Chen, Wanjia; Fu, Chaoying; Si, Chenfang; Zhang, Yaoyang; Geng, Yang; Chen, Yelin (eLife, 2025)
Aβ is believed to play a significant role in synaptic degeneration observed in Alzheimer’s disease and is primarily investigated as a secreted peptide. However, the contribution of intracellular Aβ or other cleavage products of its precursor protein (APP) to synaptic loss remains uncertain. In this study, we conducted a systematic examination of their cell-autonomous impact using a sparse expression system in rat hippocampal slice culture. Here, these proteins/peptides were overexpressed in a single neuron, surrounded by thousands of untransfected neurons. Surprisingly, we found that APP induced dendritic spine loss only when co-expressed with BACE1. This effect was mediated by β-CTF, a β-cleavage product of APP, through an endosome-related pathway independent of Aβ. Neuronal expression of β-CTF in mouse brains resulted in defective synaptic transmission and cognitive impairments, even in the absence of amyloid plaques. These findings unveil a β-CTF-initiated mechanism driving synaptic toxicity irrespective of amyloid plaque formation and suggest a potential intervention by inhibiting the endosomal GTPase Rab5.
Keywords: Alzheimer's disease; amyloid precursor protein; synapse; β-CTF; endosome